Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3233/aac-170032
|View full text |Cite
|
Sign up to set email alerts
|

Towards a framework for computational persuasion with applications in behaviour change1

Abstract: Abstract. Persuasion is an activity that involves one party trying to induce another party to believe something or to do something. It is an important and multifaceted human facility. Obviously, sales and marketing is heavily dependent on persuasion. But many other activities involve persuasion such as a doctor persuading a patient to drink less alcohol, a road safety expert persuading drivers to not text while driving, or an online safety expert persuading users of social media sites to not reveal too much pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 106 publications
0
27
0
1
Order By: Relevance
“…While there has been some interest in bringing computation to semiotics as surveyed in 1.2, and a number of recent papers in automated persuasion [16,17,26,34], we believe the rising pressure on individuals to process the vast number of informal arguments they encounter every day warrants more work in this area. How often, for example, is an argument glimpsed on the internet processed to completion?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there has been some interest in bringing computation to semiotics as surveyed in 1.2, and a number of recent papers in automated persuasion [16,17,26,34], we believe the rising pressure on individuals to process the vast number of informal arguments they encounter every day warrants more work in this area. How often, for example, is an argument glimpsed on the internet processed to completion?…”
Section: Resultsmentioning
confidence: 99%
“…• A sociologist wonders if their article is more likely to be accepted by a British or American journal • A politician wants to know how to best appeal to those on the opposing side of gun control by analysing Twitter data Natural language processing (NLP) provides tools that may assist in such tasks ad hoc by modelling lexical choices and classifying them in terms of relevance, topic, or sentiment, or in specialised components for systems for argument finding and invention [41] or automated persuasion [16,17]. The process of selecting soda can colours, for example, might be aided by analysing social media posts as an exercise in audience analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Persuasion is an activity that involves one party (the persuader) trying to induce another party (the persuadee) to believe (or not believe) certain information or to do (or not do) some action. In our context, persuasion is unidirectional [19] and focused on a "targeted argument", the aim being for the persuader to increase the ranking of this argument. The assumption is that it makes it more likely for the persuadee to believe the targeted fact (e.g., practizing exercise is good for your health) or perform the targeted action (e.g., buy a specific car).…”
Section: Ranking-based Semantics and Existing Persuasion Principlesmentioning
confidence: 99%
“…The assumption is that it makes it more likely for the persuadee to believe the targeted fact (e.g., practizing exercise is good for your health) or perform the targeted action (e.g., buy a specific car). It has been observed that the three-valued approach of Dung was too restrictive in that context [19], and thus ranking-based approaches can be more appropriate.…”
Section: Ranking-based Semantics and Existing Persuasion Principlesmentioning
confidence: 99%
“…An automated persuasion system (APS) is a system that can engage in a dialogue with a user (the persuadee) in order to persuade the persuadee to accept a specific argument (the persuasion goal) that encapsulates the reason for a change of behaviour in some specific respect [41]. For example, the persuasion goal might be that the user needs to eat fruit in order to be more healthy, and the system presents supporting arguments (based on evidence, expert opinion, explanation of the fit with the user's goals, etc.)…”
Section: Automated Persuasion Systemsmentioning
confidence: 99%